(untitled) (Journal of Engineering, 2009)
This study investigates the effects of the presences of harmonics in the exciting voltage when using a dc/ac inverter on the performance of a single-phase induction motor, the investigation includes theoretical and experimental parts and together with performance comparison of the motor with the nominal sinusoidal input voltage. The computed performance of the motor depend on the theoretical equivalent circuits which are modified to take into account the existence of harmonics in the inverter output to compute the performance at each harmonic order. It conclude from the analysis that the pulsating torque is inherent in single-phase induction motor even when supplied from a sinusoidal voltage source. Particular attention has been devoted to the pulsating torque when the motor is supplied from an inverter and the most important pulsations have been identified. The comparisons of simulation and measured results show good correlation between them in addition that it highlight and identify the cumulative effects of harmonics on the motor performance.